Sustainability assessment : rating system framework for best practices - Poveda, C. A. (Emerald Publishing Limited, 2017)
Concerns about environmental, social, economic, health, and other impacts in the building industry have led to the development of a number of environmental and sustainability assessment approaches, strategies, models, appraisals, and methodologies. Green technology and practices have been implemented to improve sustainable development performance and yield economic, social, and environmental benefits and a series of environmental and sustainability rating systems (ESRSs) have been developed around the world and used extensively with unquestionable benefits to stakeholders in the building industry. Such systems beg to be adapted and implemented in other industry contexts still seeking suitable tools with which to effectively communicate their commitment to a sustainable future and gain the social license to operate. Sustainability Assessment: A Rating System Framework for Best Practices shows how this can be done. It makes the case for the development and implementation of ESRSs in new industry contexts ranging from , manufacturing and transportation to mining and energy putting forward a new project sustainability rating system framework to assess the sustainability of a wide variety of organizations and projects. This assessment framework includes but is not limited to regulatory requirements, and includes approaches for measuring sustainability on social, economic, environmental, and health grounds. This book will be of interest to researchers and practitioners across a wide range of disciplines and industries. Scientists will find technical insights here that can further research while practitioners will find that they can implement the framework in any type of organization or project in order to address stakeholders' needs and expectations while achieving their short, mid, and long term sustainability vision and goals.
Includes index.
Keywords: Sustainable development.; Economics.; Business & Economics -- Development -- Sustainable Development.; Business & the environment, 'Green' approaches to business.; elektronické knihy; electronic books